Characterization and source apportionment of harbor-derived atmospheric PAHs and the potential risk for public and marine ecosystem health - Liying Peng; Xueou Wang; Yuehua Zuo; Junming Chen; Xudong Cui; Wenzhe Xu; Guicheng Zhang; Jun Sun (Marine Pollution Bulletin, 2026)

Emerging proglacial lake constraints on mercury transport and transform patterns in glacial meltwater runoff on China's Tibetan plateau - Xuejun Sun; Qianggong Zhang; Jie Wang; Binglin Zhang; Junming Guo; Kun Zhang; Mingyue Li; Zijian Lu; Jianbo Shi; Shichang Kang (Journal of Environmental Sciences, 2026)

Dietary phytosterol modulates antioxidant and immune-related responses in juvenile Litopenaeus vannamei fed low-fishmeal diets - Mrope Peter; Melati Sukma; Yuxuan Ma; Hector Victor Vedasto; Hongjie Xie; Zhongchao Pan; Minhao Xia; Paihuai Ouyang; Fenggang Sun; Junming Deng; Beiping Tan; Shiwei Xie (Fish & Shellfish Immunology, 2026)

Characterization, source apportionment, and health risk assessment of atmospheric particulate-bound mercury in Bishkek, Kyrgyzstan - Liujian Liao; Jie Huang; Pengfei Chen; Shiwei Sun; Tanuj Shukla; Salamat Abdyzhapar uulu; Shichang Kang; Junming Guo (Environmental Pollution, 2026)

Occurrence and characteristics of organochlorine pesticides from soils due to permafrost thaw slumping on the Qinghai-Tibetan Plateau - Xiaoyue Zhang; Lili Yang; Shiwei Sun; Shichang Kang; Junming Guo; Chenyan Zhao; Qingyu Guo; Minghui Zheng; Guorui Liu (Journal of Environmental Sciences, 2026)

High-resolution HPLC-MS/MS profiling of group A and group B seed saponins in 711 diverse soybean germplasms - Adebabay Tazeb; Shengrui Zhang; Yanan Hou; Azhar Iqbal; Aimal Nawaz Khattak; Muhammad Ahsan; Emmanuel Kofi Sie; Jing Li; Bin Li; Junming Sun (Food Chemistry, 2026)

A novel TaqMan-based RT-qPCR assay for the detection of PEDV and discrimination of the G2c subtype - Yicong Fan; Xiang Li; Jiawen Mo; Liang Weng; Shiyu Liu; Xu Song; Rongli Guo; Wei Wang; Mi Hu; Shanshan Yang; Yongxiang Zhao; Baochao Fan; et al. (Archives of Virology, 2026)

BmC-LZM-like2/4 mediates antiviral defense against BmNPV via dorsal pathway - Junming Xia; Yifan Yang; Shigang Fei; Yigui Huang; Jiasheng Lin; Luc Swevers; Min Feng; Jingchen Sun (Pesticide Biochemistry and Physiology, 2026)

3D hybrid chiral metamaterial with diverse lateral deformation behaviors: Theoretical, experimental, and numerical study - Yu Zhang; Weizhu Yang; Peijie Sun; Junming Huang; Na Yang; Lei Li (Engineering Structures, 2026)

Natural and anthropogenic factors exacerbating mercury ecological risk in the Qilian Mountain Rivers: A threat to water resources - Xiwen Miao; Shiwei Sun; Zhengzheng Yang; Shichang Kang; Yulan Zhang; Qianggong Zhang; Tanuj Shukla; Junming Guo; Yujiao Zhao; Jie Huang (Science China Earth Sciences, 2026)

Massage therapy modulates energy metabolism and alleviates skeletal muscle spasms in rats - Jiawei Sun; Changhe Yu; Yang Zhang; Fenglin Li; Yanhua Wang; Eryang Liu; Junming Guo; Xiyou Wang; Zhifeng Liu (Tissue and Cell, 2026)

Lactylation-mitochondria axis in chronic kidney disease: metabolic reprogramming, epigenetic dysregulation, and therapeutic potential - Yukun Gan; Junming Zhang; Xiushuo Fu; Yan Wang; Chenfei Zhao; Yuwen Dai; Huimin Yan; Qiong Liu; Wenjuan Sun; Limin Liu (Molecular and Cellular Biochemistry, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Spatial distribution, influencing factors, and environmental risk assessments of mercury in surface soils over Xinjiang, northwestern China - Zhengzheng Yang; Shiwei Sun; Xiwen Miao; Shichang Kang; Pengfei Chen; Dipesh Rupakheti; Zhaofu Hu; Junming Guo (Journal of Environmental Sciences, 2025)

Purification and recovery of phosphate wastewater via Fe-modified activated carbon derived from waste phenolic distillation residue - Zhe Zhou; Haiyang Sun; Chunlong Qiu; Yeyang Ni; Xiang Wang; Jianjun Zhu; Junming Chen; Zhaoyang Fei; Qing Liu; Xu Qiao (Journal of Environmental Chemical Engineering, 2025)

The evolution of research at the intersection of industrial ecology and artificial intelligence - Yongyue Gong; Fengmei Ma; Heming Wang; Asaf Tzachor; Wenju Sun; Junming Zhu; Gang Liu; Heinz Schandl (Journal of Industrial Ecology, 2025)
The intersection of artificial intelligence (AI) and industrial ecology (IE) is gaining significant attention due to AI's potential to enhance the sustainability of production and consumption systems. Understanding the current state of research in this field can highlight covered topics, identify trends, and reveal understudied topics warranting future research. However, few studies have systematically reviewed this intersection. In this study, we analyze 1068 publications within the IE–AI domain using trend factor analysis, word2vec modeling, and top2vec modeling. These methods uncover patterns of topic interconnections and evolutionary trends. Our results identify 71 trending terms within the selected publications, 69 of which, such as “deep learning,” have emerged in the past 8 years. The word2vec analysis shows that the application of various AI techniques is increasingly integrated into life cycle assessment and the circular economy. The top2vec analysis suggests that employing AI to predict and optimize indicators related to products, waste, processes, and their environmental impacts is an emerging trend. Lastly, we propose that fine‐tuning large language models to better understand and process data specific to IE, along with deploying real‐time data collection technologies such as sensors, computer vision, and robotics, could effectively address the challenges of data‐driven decision‐making in this domain.

Deciphering the transcriptional regulatory networks of FOX genes in nitrite-induced spleen injury in largemouth bass - Yan Sun; Dayong Xu; Xi Chen; Junming Zhou; Changwei Jiang; Zhiqiu Huang; Dongming Qi (Aquatic Ecology, 2025)

Characterization of PFOA isomers from PFAS precursors and their reductive defluorination - Jun Sun; Wanutcha Lorpaiboon; Nicholas Fox; Adele Jones; Junming Ho; Michael J. Manefield; Naresh kumar; Denis O'Carroll; Matthew Lee (Water Research, 2025)

Co-analysis of total suspended particles and discharge reveals the dynamic of mercury input into glacier meltwater runoff in the northern Tibetan Plateau - Jie Wang; Junming Guo; Xuejun Sun; Mingyue Li; Yushuo Liu; Zijian Lu; Shichang Kang; Qianggong Zhang (Science of The Total Environment, 2024)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

Mercury export from a glacier-fed river of Mt. Meili, southeastern Tibetan Plateau - Tao Pu; Yanlong Kong; Shichang Kang; Shijin Wang; Junming Guo; Jia Jia; Kunpeng Wu; Xiaoyi Shi; Ke Wang; Shiwei Sun; Wenjie Li (Journal of Hazardous Materials, 2024)

Westerlies-driven transboundary transport of atmospheric mercury to the north-central Tibetan Plateau - Shiwei Sun; Ming Ma; Junming Guo; Xiaobo He; Xiufeng Yin; Tao Sun; Qianggong Zhang; Shichang Kang (Science of The Total Environment, 2024)

The structure and bioactivities of Stemona alkaloids and alkaloids with [1,2-α] azepine nucleus (2009–2021) - Yang Xu; Junming Liang; Yushu Yan; Dejuan Sun; Hua Li; Lixia Chen (Phytochemistry Reviews, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Single-nucleus sequencing of silkworm larval midgut reveals the immune escape strategy of BmNPV in the midgut during the late stage of infection - Junming Xia; Shigang Fei; Yigui Huang; Wenxuan Lai; Yue Yu; Lingying Liang; Hailin Wu; Luc Swevers; Jingchen Sun; Min Feng (Insect Biochemistry and Molecular Biology, 2024)

Effect of Small-Scale Topographical Variations and Fetch from Roughness Elements on the Stable Boundary Layer Turbulence Statistics - Sudheer R. Bhimireddy; Jielun Sun; Junming Wang; David A. R. Kristovich; April L. Hiscox (Boundary-Layer Meteorology, 2024)
Understanding the influence of roughness and terrain slope on stable boundary layer turbulence is challenging. This is investigated using observations collected from October to November of 2018 during the Stable Atmospheric Variability ANd Transport (SAVANT) field campaign conducted in a shallow sloping Midwestern field. We analyze the turbulence velocity scale and its variation with the mean wind speed using observations up to 10–20 m on four meteorological towers located along a shallow gully. The roughness length for momentum over this complex terrain varied with wind direction from 0.0049 m to a maximum of 0.12 m for winds coming through deciduous trees present in the field. The variation of the turbulence velocity with wind speed shows a transition from a weak wind regime to a stronger wind regime, as reported by past studies. This transition is not observed for winds coming from the tree area, where turbulence is enhanced even for weak wind speeds. For weak stratification and stronger winds, the turbulent velocity scale increased with an increase in roughness while the terrain slope is seen to have a weak influence. The sizes of the dominant turbulent eddies seen from the vertical velocity power spectra are observed to be larger for winds coming through the tree area. The turbulence enhancement by the trees is found to be strong within a fetch distance of 7 times the tree height and not observable at 16 times of the tree height.

Mapping research trends and identifying missing research gaps in green environment and public health: a bibliometric analysis for 2003–2021 - Huiling Wang; Fei Sun; Junming Su; Sanchir Bold; Mansoor Ahmed Koondhar (Environment, Development and Sustainability, 2023)

Hypoxia enhances steroidogenic competence of buffalo (Bubalus bubalis) granulosa cells - Yu Zhang; Jun Zhang; Junming Sun; Yiqiang Ouyang; Deshun Shi; Fenghua Lu (Theriogenology, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Identification of quantitative trait loci and candidate genes for seed folate content in soybean - Kwadwo Gyapong Agyenim-Boateng; Shengrui Zhang; Rongzhe Gu; Shibi Zhang; Jie Qi; Muhammad Azam; Caiyou Ma; Yecheng Li; Yue Feng; Yitian Liu; Jing Li; Bin Li; et al. (Theoretical and Applied Genetics, 2023)

Insight into the relationships between total suspended particles and mercury in meltwater in a typical glacierized basin in the inland Tibetan Plateau - Xuejun Sun; Qianggong Zhang; Mingyue Li; Jie Wang; Zijian Lu; Junming Guo; Shichang Kang; Jianbo Shi (Journal of Hazardous Materials, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Identification of genes for seed isoflavones based on bulk segregant analysis sequencing in soybean natural population - Muhammad Azam; Shengrui Zhang; Yuanyuan Huai; Ahmed M. Abdelghany; Abdulwahab S. Shaibu; Jie Qi; Yue Feng; Yitian Liu; Jing Li; Lijuan Qiu; Bin Li; Junming Sun (Theoretical and Applied Genetics, 2023)

Vasorin contributes to lung injury via FABP4-mediated inflammation - Xiaoping Guo; Junming Sun; Jinning Liang; Siran Zhu; Mingyuan Zhang; Lichao Yang; Xuejing Huang; Kangning Xue; Zhongxiang Mo; Sha Wen; Bing Hu; Jiajuan Liu; et al. (Molecular Biology Reports, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Immune characteristics distinguish patients with severe disease associated with SARS-CoV-2 - Xiaolei Li; Yang Liu; Junming Li; Longhua Sun; Jibin Yang; Fei Xu; Jing Zhou; Lagen Wan; Xinping Xu; Aiping Le; Wei Zhang (Immunologic Research, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Concentration, spatiotemporal distribution, and sources of mercury in Mt. Yulong, a remote site in southeastern Tibetan Plateau - Rukumesh Paudyal; Shichang Kang; Lekhendra Tripathee; Junming Guo; Chhatra Mani Sharma; Jie Huang; Hewen Niu; Shiwei Sun; Tao Pu (Environmental Science and Pollution Research, 2019)

Validation results of maximum S4 index in F-layer derived from GNOS on FY3C satellite - Weihua Bai; Yueqiang Sun; Junming Xia; Guangyuan Tan; Cheng Cheng; Guanglin Yang; Qifei Du; Xianyi Wang; Danyang Zhao; Yusen Tian; Xiaoxin Zhang; Mi Liao; et al. (GPS Solutions, 2019)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

Mercury Concentrations in the Fish Community from Indrawati River, Nepal - Aastha Pandey; Chhatra Mani Sharma; Shichang Kang; Qianggong Zhang; Lekhendra Tripathee; Junming Guo; Xiaofei Li; Shiwei Sun; Rukumesh Paudyal; Prakash Acharya; Mika Sillanpää (Bulletin of Environmental Contamination and Toxicology, 2017)

High-resolution mapping of QTL for fatty acid composition in soybean using specific-locus amplified fragment sequencing - Bin Li; Shengxü Fan; Fukuan Yu; Ying Chen; Shengrui Zhang; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Theoretical and Applied Genetics, 2017)

Distribution and variation of mercury in frozen soils of a high-altitude permafrost region on the northeastern margin of the Tibetan Plateau - Shiwei Sun; Shichang Kang; Jie Huang; Shengyun Chen; Qianggong Zhang; Junming Guo; Wenjie Liu; Bigyan Neupane; Dahe Qin (Environmental Science and Pollution Research, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Analysis of additive and epistatic quantitative trait loci underlying fatty acid concentrations in soybean seeds across multiple environments - Shengxu Fan; Bin Li; Fukuan Yu; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Euphytica, 2015)
Soybean is one of the most important oilseed crops in the world. The soybean oil contains various fatty acids. Their concentrations determine the quality and nutritional value of soybean oil. On the other hand, quantitative trait loci (QTL) mapping for the concentrations of soybean predominant fatty acids could provide the genetic basis for soybean fatty acid composition. In this study, a soybean genetic linkage map was constructed based on 161 polymorphic SSR markers in recombinant inbred lines (RILs) derived from a cross of cv. Luheidou2 × Nanhuizao. By using this map, 35 additive QTLs underlying individual fatty acid concentrations were identified in single environment, while 17 additive QTLs were identified underlying specific fatty acids across multiple environments or underlying multiple fatty acids. Fifteen of the 52 loci were found to be novel loci, explaining 5–24 % of phenotypic variation. Moreover, 25 epistatic QTLs were identified and explained a high phenotypic variation for the fatty acid concentrations, suggesting an essential role of epistatic effect for fatty acid concentrations. The identification of additive and epistatic QTLs suggested a complex network for soybean fatty acid concentrations, and will facilitate the understanding for fatty acid accumulation.

Slab break-off model for the Triassic syn-collisional granites in the Qinling orogenic belt, Central China: Zircon U-Pb age and Hf isotope constraints - Zhiwei Bao; Christina Yan Wang; Lingjun Zeng; Weidong Sun; Junming Yao (International Geology Review, 2015)

Prevalence and genotype distribution of human papillomavirus infection in Harbin, Northeast China - Bowen Sun; Junming He; Xiaohang Chen; Meihui He; Zhangxiu He; Yan Wang; Qinglong Shang; Libo Yu; Lanlan Wei (Archives of Virology, 2014)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Molecular cloning, characterization and differential expression of Cdc42 in Fonsecaea monophora - Zhi Xie; Peiying Feng; Junming Zhang; Xiqing Li; Jiufeng Sun; Changming Lu; Huaiqiu Huang; Liyan Xi (Molecular Biology Reports, 2012)

Identification of new T1BL.1RS translocation lines derived from wheat (Triticum aestivum L. cultivar “Xiaoyan No. 6”) and rye hybridization - Jun Ji; Zhiguo Wang; Jiazhu Sun; Junming Li; Xiangqi Zhang; Daowen Wang; Aimin Zhang (Acta Physiologiae Plantarum, 2008)